P3_2 An Extreme Solution to Global Warming - Kuzemczak, Jacek; Houghton, Kate; Clark, Ashley; Simms, Henry (Physics Special Topics, 2012)
<!– @page margin: 2cm P margin-bottom: 0.21cm; direction: ltr; color: #000000; widows: 2; orphans: 2 P.western font-size: 12pt; so-language: en-GB P.cjk font-size: 12pt; so-language: en-US P.ctl font-size: 12pt A:link color: #0000ff A.cjk:link so-language: zxx A.ctl:link so-language: zxx –> A brief investigation into the plausibility of solving the issue of global warming by moving the Earth further away from the Sun. It was found that the Earth would need to be moved to 1.23 AU to compensate for a 6.4 K per century increase in temperature.